The Design of Application Architecture of the Institute of Business Based on Enterprise Architecture Planning - Muhammad Yusuf Morais; Habibullah Akbar (Department of Electrical Engineering and Information Technology,Faculty of Engineering UGM, 2018)
Institute of Business (IOB) is committed to achieve its goals, i.e. becomes a place for economics and business as well as computer science developers, and prepare a ready-to-use Human Resources (HR), especially for Timor Leste. At present, IOB does not have an alignment between business processes and information systems owned. Therefore, this paper proposes an architectural design that bridges the alignment. The methods used to build the framework are include Enterprise Architecture Planning (EAP), SWOT, Value Chain, and Mc Farlan Grid. The built frameworks are focused on the needs of the application architecture. The resulted portfolio has 45 applications for various divisions of IOB. In addition, the SWOT analysis shows that IOB's internal and external factors are in the second quadrant. Thus, IOB's position is relatively strong, though it is facing a big challenge. The recommended strategy is the Strengths-Threats (ST) strategy that uses the company’s strength to overcome the threats. This strategy includes improving facilities, adding faculties and departments, developing academic information systems, improving the quality of learning, and improving the human resources quality.